Corporate Governance Influence on Sustainable Financial Management in Emerging Markets - Dwi Dewianawati; Erry Setiawan (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Corporate governance has emerged as a strategic issue in ensuring the sustainability of financial management, particularly in emerging markets that face governance challenges and increasing global pressure to adopt sustainable practices. This study aims to examine the effect of corporate governance on sustainable financial management by emphasizing the role of governance mechanisms in promoting long-term oriented financial performance. The study employs an explanatory quantitative approach using secondary data obtained from the annual reports and sustainability reports on the IDX over the period 2020–2024. Corporate governance mechanisms are measured through the proportion of independent commissioners, board of directors’ size, institutional ownership, and the existence of an audit committee, while sustainable financial management is proxied by sustainable profitability, profit persistence, and ESG-based investment intensity. Data were analyzed using panel regression techniques with fixed effect and random effect models, complemented by robustness tests to ensure the consistency of the results. The findings indicate that corporate governance has a significant influence on sustainable financial management, particularly through the role of independent boards and audit committees in enhancing transparency and efficiency in financial decision-making. The study concludes that strong governance practices contribute to improving corporate financial resilience and supporting sustainability agendas in emerging markets.